Deepening understanding of prior knowledge: what diverse first-generation college students in the U.S. can teach us. Issue 5 (4th July 2017) - Castillo-Montoya, Milagros
ABSTRACT: Educational research indicates that teachers revealing and utilizing students' prior knowledge supports students' academic learning. Yet, the variation in students' prior knowledge is not fully known. To better understand students' prior knowledge, I drew on sociocultural learning theories to examine racially and ethnically diverse college students' sociopolitical prior knowledge, a component of sociopolitical consciousness. In this qualitative study, I interviewed 18 first-generation college students in the U.S. who were enrolled in two introductory undergraduate sociology courses. Study participants identified as African-American, Latino, and/or White. The study reveals that students' sociopolitical prior knowledge is comprised of awareness and understanding and it varies by topic of discussion. Further, college students' sociopolitical prior knowledge is informed by lived experiences and can relate to subject-matter content. Implications for teaching and learning include having a deepened sense of novice learners' modes of thinking.